The Effects of Strength Training on Gait Function in Patients with Multiple Sclerosis: A Narrative Review - Kimla, Witold; Hajok, Natalia; Maruszak, Anna; Kwiecień, Julia; Stołtny, Julia; Goryczka , Justyna; Lisik, Magdalena; Mida, Magdalena; Michalik, Magdalena; Majda, Urszula (Journal of Education, Health and Sport, 2026)
Introduction: Multiple sclerosis (MS) is a chronic immune-mediated demyelinating disease of the central nervous system and a leading cause of non-traumatic disability in young adults. Gait impairment is one of the most common and disabling symptoms, significantly affecting functional independence and quality of life. Purpose of the work: The aim of this narrative review was to summarize and critically evaluate current evidence on the effects of strength training on gait function in individuals with multiple sclerosis. Materials and methods: A narrative literature review was conducted using PubMed, Scopus, and Google Scholar. Original research and review articles published between 2000 and 2025 were identified using the keywords multiple sclerosis, strength training, resistance training, gait, and walking. Studies were selected based on thematic relevance and clinical applicability. In total, 21 studies were included in the analysis. Results: The reviewed studies consistently demonstrated improvements in muscle strength following strength training, particularly in individuals with mild to moderate disability. However, the effects of isolated strength training on gait function were inconsistent. Multimodal rehabilitation programs incorporating strength training more frequently resulted in improvements in gait speed, endurance, and functional walking measures. Conclusions: Strength training effectively improves muscle strength in people with MS, while its isolated impact on gait remains inconclusive. Multimodal rehabilitation approaches appear to provide more consistent benefits for gait function, highlighting the need for standardized outcome measures and further research.